IMPLEMENTASI INSTRUKSI DIRJEN BIMAS ISLAM NOMOR: Kep/D/101/1978 TENTANG TUNTUNAN PENGERAS SUARA DI MASJID, LANGGAR, DAN MUSHOLA DALAM KONTEKS PLURALISME DAN PERSPEKTIF HUKUM TATA NEGARA ISLAM (Studi Kasus Masyarakat Kota Medan) - Muhammad Zikri Abdillah; Afrian Raus (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The main problem in this study is how is the condition of religious communities after the circulation of the Directive of the Guidance and Guidance of the Islamic Community Guidance Number: Kep/D/101/1978 on Guidance for Loud Speakers in Mosques, Langgar and Mushola and how it is implemented in the context of pluralism and then see the policy in terms of perspective Islamic constitutional law. The purpose of this study is to describe how the conditions of worship of religious people before and after the circulation of the circular letter and to know how the implementation of the circular Directive Directorate General of Islamic Community Guidance Number: Kep / D / 101/1978 about Guidelines for Loud Speakers in the Mosque, Langgar, and Mushola for realizing what was instructed in the circular.